Sikap Multikulturalisme Konselor Sekolah - Endang Rifani; Susilawati Susilawati; Weni Anggraini (Kuras Institute, 2022)
Multiculturalism attitude of school counselors is an attitude that can support the effectiveness of guidance and counseling programs in schools in establishing relationships with stakeholders, collaborating with parents, community leaders, and other professionals. The purpose of this study is to determine the level of multiculturalism in school counselors. The type of research is survey research, the research was conducted using the Indonesian version of the The Multicultural School Counseling Behavior Scale (MSCBS), the research subject is school counselors in Brebes Regency. The results of this study indicate that overall school counselors have a high attitude of multiculturalism in each research indicator, the details of the results and discussion are contained in this article.